The impact of interventions by pharmacists collected in a computerised physician order entry context: a prospective observational study with a 10-year reassessment - Marie-Caroline Loustalot; Sarah Berdot; Pierre Sabatier; Pierre Durieux; Germain Perrin; Alexandre Karras; Brigitte Sabatier (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY